Moral Distress Thermometer: Translation and Validation in Greek - Aglaia Katsiroumpa; Ioannis Moisoglou; Olympia Konstantakopoulou; Elisavet Papasimakopoulou; Parisis Gallos; Maria Tsiachri and Petros Galanis (Professor Despina Sapountzi-Krepia, 2024)
Moral Distress Thermometer: Translation and Validation in Greek